Pengaruh Layanan Konseling Melalui Media Audio Visual terhadap Motivasi Belajar Siswa - Muhammad Hafiz Maulana (Primary Journal of Multidisciplinary Research, 2026)
The developments of the times make teachers innovate the learning process, includes in provide counseling services. As the front guard in help students with personal, social and academic problems. Counseling guidance teachers are required to provide services that are interesting, and effective. This counseling is presented through audio visual media, so the counselee (students) doesn't feel bored, able to capture the message from counselor (BK teacher). This study aims to determine and analyze the influence of counseling service through audio visual media to student learning motivation. This metode of research is literature review analysis techniques with found counseling service through audio visual media has a positive effect to student learning motivation.